Prevalence of Pre-Hypertension/Hypertension and Its Associated Factors Among Adults in the Wolaita Zone of Southern Ethiopia: A Cross-Sectional Study - Eshetu Elfios Endrias MSc; Teketel Tesfaye Mamito MSc; Temesgen Geta Hardido MSc; Bizuayehu Atinafu Ataro MSc (SAGE Publishing, 2024)
Preventing the development of high blood pressure and resulting complication requires estimating the prevalence of prehypertension/hypertension and identifying associated risk factors. Information about pre-hypertension/hypertension in Ethiopia, especially in the southern region, is scarce, and limited knowledge exists regarding the prevalence and risk factors associated with pre-hypertension/hypertension. Objective of this study was to assess prevalence of pre-hypertension/hypertension and its associated factors among adults in Wolaita Zone of Southern Ethiopia, 2023. This cross-sectional study was conducted among adults attending outpatient departments in governmental hospitals in South Ethiopia in 2023. Face-to-face interviews were used to gather information on sociodemographic data, dietary and behavioral patterns, and medical history. Digital weighing scales, Stadiometers, and digital sphygmomanometers were used to measure height, blood pressure, and weight, respectively. Epi-Data version 3.1 was used to enter the data before exporting it to SPSS version 25 for analysis. To find factors associated with prehypertension/hypertension, binary logistic regressions were conducted and odds ratios with 95% confidence intervals were computed. The overall prevalence of prehypertension/hypertension was 42.8% (95% confidence interval: 39.56, 49.47). Factors associated with prehypertension/hypertension in this study were older age, male gender, obesity, diabetes mellitus comorbidity, alcohol drinking, and family history of hypertension. Lifestyle modification is demanded for pre-hypertensive/hypertensive patients to prevent progression to severe complications, including premature death and permanent disabilities.